Mediating Effect of Strategy Implementation on the Relationship Between TMT Characteristics and Performance of Ugandan State Agencies - Arthur Nuwagaba; Owino Joseph; Caren Angima; Vincent Machuki (European Scientific Journal, ESJ, 2022)
The aim of this study is to determine the mediating effect of strategy implementation of the relationship between TMT characteristics and performance of Ugandan state agencies. The study was anchored on the upper echelons’ theory and dynamic capabilities theory. The study adopted a descriptive cross-sectional research design. The target population of the study was the 201 state agencies in Uganda. The study adopted at least three members of the TMT depending on the number of TMT members of the 160 selected state agencies in Uganda to gather the required information. Primary data was gathered using a structured questionnaire that was administered online. Inferential statistics employed regression analysis to test the hypothesis and draw conclusions. Haye’s (2022) PROCESS 4 (model 4) was utilised to test the hypothesis of this study. Furthermore, strategy implementation partially mediates the relationship between TMT characteristics and performance (Indirect effect of strategy implementation, b=.385, p<0.05 and the direct effect, b = .267, p<0.05). From the findings of this study, the research concludes that that strategy implementation has a significant partial mediating effect on the relationship between TMT characteristics and the performance of Ugandan state agencies. In addition, the results imply that the specific mechanism by which the connection between TMT characteristics and the performance of Ugandan state agencies occurs is direct, strategy implementation contributes a part to the relationship. This study recommends that individuals that make the TMT should have significant expert capabilities that give relevance while formulating and executing strategies. The study also recommends that strategy implementation should have a framework that is not affected by politics and corruption. This study also recommends that state agencies in Uganda need to create a prize and acknowledgement framework for TMTs and personnel who succeed in strategy implementation so they can be persuaded. This is on the grounds that it is through strategy implementation that the state agencies in Uganda can follow through on their directives and further improve service delivery. Rewards give a chance to the TMTs and staff to contend among themselves and this would bring quality, efficiency, proficiency and adequacy in delivering services.